U.S. Free Trade Agreements and Enforcement of Labor Law in Latin America - Sabina Dewan; Lucas Ronconi (Inter-American Development Bank (IDB), 2014)
This paper analyzes whether Free Trade Agreements (FTAs) signed between the United States and Latin American countries during the last decade produced higher enforcement of labor regulations. The paper computes before-after estimates of the effect of FTAs on labor inspections and exploits variation across countries using non-signers as a comparison group. The empirical strategy benefits from the fact that about half of Latin American countries have signed a trade agreement with the United States. Difference-in-differences estimates suggest that signing an FTA produced a 20 percent increase in the number of labor inspectors and a 60 percent increase in the number of inspections. The North American Free Trade Agreement (NAFTA), however, does not appear to have the same positive impacts on Mexico. The paper concludes with a discussion of these results.
hdl:11319/6724
Keywords: F16; J83; K31; 330; Enforcement; Labor; Trade; Latin America